Stem cells in breast milk - Kuciel, Natalia; Mazurek, Justyna; Czosnykowska-Łukacka, Matylda; Królak-Olejnik, Barbara (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Stem cells represent 10-15% of all cells that appear in breast milk. They participate in the mechanisms that control the homeostasis and processes self-healing of tissues in neonates. The first reports on the presence of stem cells in breast milk appeared in 2007. Stem cells exceed the barrier in the intestine, migrate to, and integrate with all body tissues and organs. The presence of the nestin marker may indicate that the stem cells in breast milk influence brain development. Populations of stem cells are extremely plastic and are able to develop into cells of all three embryonic layers (neurons, hepatocytes, pancreatic cells, osteoblasts, chondrocytes, heart cells, and adipocytes). Stem cells from breast milk may be used in regenerative medicine due to the huge potential of tissues from all three embryonic leaves. Stem cells from breast milk do not form tumours after implantation into animal tissues; moreover, their collection and transportation are non-invasive, safe, and ethical.